Investigação teórica e experimental do comportamento de vigas mistas de aço e concreto protendidas - Almeida, Marcela Moreira da Rocha (2023)
Steel-concrete composite beams composed by an association of steel profile with conventional concrete slab or with profiled sheeting are widely used as a structural solution with familiar construction technology. The use of external prestressing in the steel profile can improve the performance of composite beams, increasing their resistance and reducing deflections. However, despite the advantages mentioned, studies or reports involving the application of prestressing technology in composite structures are rare, and in the case of externally prestressed composite beams with profiled sheeting, there are no references available. In this context, the present work aims to investigate the behavior of simply supported externally prestressed steel-concrete composite beams under positive bending moment, through the development of experimental, numerical and analytical studies. Initially, a bibliometric analysis and literature review were conducted on works involving prestressed steel-concrete composite beams, to identify the main knowledge gaps in the area. Then, an analytical methodology for the analysis and design of prestressed composite beams was presented, in addition to the explanation of constructive aspects inherent to the system. Furthermore, numerical models that to adequately simulate the behavior of prestressed steel-concrete composite beams were assembled and calibrated. Then, an experimental program consisting of two prestressed composite beams with straight and draped tendon profiles and a reference beam without prestressing was developed. Finally, a parametric study was carried out to characterize the behavior and influence of several variables in the system, such as: positioning and shape of tendons, initial prestressing force, beam and tendons length and type of steel profile. The results showed that the presented analytical methodology and the proposed numerical model were adequate to predict the behavior of prestressed composite steel-concrete beams and presented a good approximation with the experimental results. The results also confirmed that the use of external prestressing in composite steel and concrete beams was efficient to increase the resistant moment and reduce deflections under service loads.